Nonsuicidal Self-Injury: Its Associations With Pathological Internet Use and Psychopathology Among Adolescents - Mészáros, Gergely; Győri, Dora; Horváth, Lili Olga; Szentiványi, Dora; Balázs, Judit (Frontiers in Psychiatry, 2020)
Background/hypotheses: As risk factors for non-suicidal self-injury (NSSI), most studies highlight the importance of internalising disorders, while only a few researches show the connection between externalising disorders and NSSI. Although some papers have introduced the idea that increasing prevalence rates of NSSI are connected to the broader use of the internet, associations between NSSI and pathological internet use (PIU) are understudied. According to our hypothesis, there is a connection between PIU and NSSI, but this is mediated by psychopathological factors from both internalising and externalising dimensions. Methods: In line with the dimensional approach of psychiatric disorders, participants (N=363) were recruited from both clinical (N=202 psychiatric inpatient) and non-clinical (N=161 adolescents from secondary schools) settings. Measurements: Demographic Questionnaire; Strengths and Difficulties Questionnaire (SDQ); Deliberate Self-Harm Inventory (DSHI); Young Diagnostic Questionnaire for Internet Addiction (YDQ), Mini International Neuropsychiatric Interview Kid (M.I.N.I. Kid). Results: The frequency of NSSI in the total sample (N=363) is 39,9% (71% girls). In NSSI frequency, there was a significant difference between ‘Normal’ users and the two pathological groups (U=5800.500 z=-2.586 p<0.017; U=2020.000 z=-2.501 p<0.017). According to the mediator model, the relationship between PIU and NSSI is mediated by psychopathological factors. Conclusions: We found a high frequency of NSSI. According to our results, PIU in itself is not a risk factor for NSSI, but might become a risk factor in the presence of comorbid psychiatric disorders. All of these findings draw the attention of clinicians to the importance of careful screening of comorbid disorders with PIU.